The Influence of Channel Member Management Program on Sales Ability of Indosat Frontliners in Banda Aceh City - Ahmad, Lukman; Mujiburahman (Indonesian Journal Economic Review (IJER), 2023)
Intense cellular business competition forces cellular operators to implement strategies such as; price strategy (cheap starter page, small nomination voucher, low tariff, national free rooming), product strategy (product innovation/features in cellular cards), promotion strategy (incessant advertising, publicity, sponsored events), and distribution strategy. In the elements of the marketing mix, the third element is place or what is often referred to as a marketing channel or distribution channel, which is included in this distribution channel which simply includes wholesalers and retailers (frontliners). Indosat, in an effort to increase its market share, is now trying something new to increase sales in the cellular business, namely through a channel member management program. The management of channel members is expected to increase the positive sales ability of cellular members to sell their cellular card products. The purpose of this study was to determine the effect of managing channel members on the selling ability of frontliners. The surveys conducted use targeted sampling techniques for sampling and are descriptive and verifiable. The sample size for this study is 100 frontliners. Data collection techniques used include questionnaires, interviews and document research. The data analysis technique used is simple linear regression. According to this study, channel member management has a positive impact of 38.8% on sales capability.